Beneficial effects of Panax notoginseng (Burkill) F. H. Chen flower saponins in rats with metabolic hypertension by inhibiting the activation of the renin-angiotensin-aldosterone system through complement 3 - Qiqi Huang; Jie Su; Jie Xu; Huanhuan Yu; Xiaohu Jin; Yajun Wang; Meiqiu Yan; Jingjing Yu; Suhong Chen; Youhua Wang; Guiyuan Lv (BMC, 2023)
Abstract Background Metabolic hypertension (MH) has become the most common type of hypertension in recent years due to unhealthy eating habits and lifestyles of people, such as over-eating alcohol, high fat, and sugar diets (ACHFSDs). Therefore, effective means to combat MH are needed. Previous studies have shown that Panax notoginseng (Burkill) F. H. Chen flower saponins (PNFS) can lower blood pressure in spontaneously hypertensive rats (SHR). However, whether it acts on MH and its mechanism of action remain unclear.  Methods The pharmacodynamic effects of PNFS were evaluated in rats with ACHFSDs-induced MH. The blood pressure, blood biochemical, grip strength, face temperature, vertigo time, and liver index were estimated. The histological changes in the liver and aorta were observed using hematoxylin and eosin staining. The levels of ET-1, TXB2, NO, PGI2, Renin, ACE, Ang II, and ALD in plasma were detected using ELISA. The levels of C3, KLF5, LXRα, and Renin in kidney tissues were measured using qRT-PCR.The expression levels of C3, KLF5, LXRα, and Renin in kidney tissues were examined using Western blotting. Results In the present study, PNFS was found to reduce blood pressure, face temperature, and vertigo time, increase grip strength and improve dyslipidemia in rats with MH. In addition, PNFS decreased the plasma levels of ET-1 and TXB2, elevated the levels of NO and PGI2, and improved pathological aortic injury. Meanwhile, PNFS decreased the plasma levels of Renin, ACE, Ang II, and ALD. QRT-PCR and Western bolt showed that PNFS downregulated C3, KLF5, LXRα, and Renin protein and mRNA expression in the kidneys of rats with MH. Conclusion The finding of the present study suggested that PNFS could downregulate C3 and KLF-5 expression in rats with MH, thereby inhibiting the overactivation of the renin-angiotensin-aldosterone system, while improving vascular endothelial function and ultimately reducing blood pressure in rats with MH.